Baker’s idiom translation strategies in translating English idioms into Vietnamese: a case study of “TO KILL A MOCKINGBIRD” - Vương, Thu Hằng (2020)
Idioms, complicated linguistic units of a language, often created considerable difficulties for translators. The study was undertaken to illuminate this linguistic phenomenon and to explore strategies that were implemented by Pham Viem Phuong and Huynh Kim Oanh in their translation of English idioms in the novel To Kill a Mockingbird. The most and least frequently used translation strategies were ascertained. Whereby, suggestions on applicable strategies of translating idioms from English into Vietnamese were provided. Both qualitative and quantitative methods were utilized in this case study. The chosen subjects went through the research process including two major procedures, data collection and data analysis. First, English idioms and Vietnamese translations were extracted and listed on a table. In the procedure of analysis, English idioms‟ type was determined, and translation strategies were identified. Next, the strategies were calculated. The most and least frequently used ones could be seen clearly through it. The findings of the study showed that idioms in the novel appear most commonly in the form of a verbal phrase, noun phrase and binomial. Most importantly, the study pointed out that among five strategies comprising exact equivalence, reduction, paraphrase and literal, the third one was most preferred by the translators. The study includes a broad theoretical background that can be a good reference for anyone who is interested and for those who find that idioms and idiom translation are complicated and difficult. It does not only imply translation strategies to cope with the problems related to idiom translation but also is a source of inspirations for further research.